Usted pregunta (Journal of Parents and Teachers, 2025)
Questions answered by Joaquín Ma. García de Dios on how to interact with beggars and how to teach children to interact with them: don't push them away, teach them to talk to them, it's very humane and very educational. On the other hand, when a parent speaks ironically about their child's friends and the child asks bitterly why they do so, they must bear in mind that irony is a weapon that hurts and is unfair. And the conflict of a mother faced with her children's mess at home. It is important that order is for the children and not the children for order.
Keywords: beggars, irony, chaos, education, parents